2022
DOI: 10.1037/xhp0000987
|View full text |Cite
|
Sign up to set email alerts
|

Statistical learning of across-trial regularities during serial search.

Abstract: Previous studies have shown that attention becomes biased toward those locations that frequently contain a target and is biased away from locations that have a high probability to contain a distractor. A recent study showed that participants also learned regularities that exist across trials: Participants were faster to find the singleton when its location was predicted by the location of the target singleton on the previous trial. Note, however, that this across-trial statistical learning was only demonstrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
19
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(29 citation statements)
references
References 110 publications
(152 reference statements)
4
19
4
Order By: Relevance
“…For example, in 'probability cuing' studies [29][30][31]58] in which a target appears more often in one region than in other regions, each time attention is directed to the target, associations are formed between the target and its location within the visual field. In a recent study investigating across trials learning it was shown that if there is no initial direction of attention to the target (for example, when search is serial rather than parallel), learning across trial regularities does not occur, but that learning can be instantiated when targets are made salient such that they pop out from the display [59]. We assume that spatial statistical learning operates by continuously adjusting weights within an assumed spatial priority map, which at any moment in time dynamically controls the deployment of covert attention and gaze [20].…”
Section: Space-versus Feature-based Suppressionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, in 'probability cuing' studies [29][30][31]58] in which a target appears more often in one region than in other regions, each time attention is directed to the target, associations are formed between the target and its location within the visual field. In a recent study investigating across trials learning it was shown that if there is no initial direction of attention to the target (for example, when search is serial rather than parallel), learning across trial regularities does not occur, but that learning can be instantiated when targets are made salient such that they pop out from the display [59]. We assume that spatial statistical learning operates by continuously adjusting weights within an assumed spatial priority map, which at any moment in time dynamically controls the deployment of covert attention and gaze [20].…”
Section: Space-versus Feature-based Suppressionmentioning
confidence: 99%
“…Even though these regularities were randomly mixed within random trial sequences, the visual system was nevertheless sensitive to these regularities and adjusted the priority landscape on a trial-by-trial basis. As indicated, a follow-up study showed that in order to learn these across-trial regularities, the target must be salient and needs to pop out from the display [59].…”
Section: More Complex Regularitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In more recent years, VSL was also investigated in the context of visual search (see Theeuwes et al, 2022 , for a recent review). It was shown that temporal predictive associations regarding spatial configurations and target locations in search displays can be implicitly learned and utilized to facilitate search (Boettcher et al, 2022 ; Li et al, 2022 ; Li & Theeuwes, 2020 ; Olson & Chun, 2001 ; Ono et al, 2005 ; Thomas et al, 2018 ; Toh et al, 2021 ). For instance, in the study by Li and Theeuwes ( 2020 ), participants were asked to search for a shape singleton target within a circular array of eight items (i.e., a diamond among seven circles or a circle among seven diamonds).…”
Section: Introductionmentioning
confidence: 99%
“…It was reasoned that if a particular location was selected (the predicting location), the weight of the predicted (i.e., expected) location on the next trial was boosted, resulting in a faster selection of the predicted location. In a follow-up study using the T -among- L s task as an operationalization of slow inefficient serial search, Li et al ( 2022 ) found that individuals did not express any RTs benefits on predicted trials. However, when observers were first exposed to the same regularities during parallel “pop-out” feature search (i.e., the target was colored differently from nontargets), across-trial VSL effects reoccurred, and the learned biases even persisted when search subsequently became inefficient and serial.…”
Section: Introductionmentioning
confidence: 99%